TINJAUAN KEBUGARAN JASMANI SISWA SEKOLAH DASAR - dessi novita sari (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
The problem in this study is that the level of physical fitness of students at SD Negeri 11 Kampung Jawa, Kota Solok is not yet known. The formulation of the problem in this study is how the level of physical fitness of students of SD Negeri 11 Kampung Jawa, Kota Solok. The purpose of this study was to determine the physical fitness of students of SD Negeri 11 Kampung Jawa, Kota Solok. The purpose of this study was to determine the physical fitness of elementary school students. The research method uses quantitative methods with survey techniques. The population is 36 and the research sample is 18 people. Data collection used a physical fitness test for Indonesian children aged 10-12 years. Based on the test results and field data findings, it can be concluded that the fifth grade students of SD Negeri 11 Kampung Jawa, Solok City. The purpose of this study was to determine the level of physical fitness of female students who were in the average group of 12 people (66.67%) , while above the average group were 4 people (22.22%) and those who were below the average were 2 people (11.11%).